2011
DOI: 10.1007/s00454-011-9342-z
|View full text |Cite
|
Sign up to set email alerts
|

Minimum Manhattan Network is NP-Complete

Abstract: Given a set T of n points in R 2 , a Manhattan network on T is a graph G with the property that for each pair of points in T , G contains a rectilinear path between them of length equal to their distance in the L 1 -metric. The minimum Manhattan network problem is to find a Manhattan network of minimum length, i.e., minimizing the total length of the line segments in the network.In this paper, we prove that the decision version of the MMN problem is strongly NP-complete, using a reduction from the well-known 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 11 publications
0
11
0
Order By: Relevance
“…and O(log n + √ r) query time, where is an arbitrarily small positive constant and r is an arbitrary integer, such that 1 < r < n. Recently, Amani et al [15] show how to compute a plane problem of finding a 1-spanner in L 1 -metric [9]. Given a rectilinear polygon with n vertices, in linear time, Schuierer [16] constructs a data structure that can report the shortest path (in L 1 -metric) for any pair of query points in that polygon in O(log +k) time where k is the number of segments in the shortest path.…”
Section: (C)mentioning
confidence: 99%
See 1 more Smart Citation
“…and O(log n + √ r) query time, where is an arbitrarily small positive constant and r is an arbitrary integer, such that 1 < r < n. Recently, Amani et al [15] show how to compute a plane problem of finding a 1-spanner in L 1 -metric [9]. Given a rectilinear polygon with n vertices, in linear time, Schuierer [16] constructs a data structure that can report the shortest path (in L 1 -metric) for any pair of query points in that polygon in O(log +k) time where k is the number of segments in the shortest path.…”
Section: (C)mentioning
confidence: 99%
“…Also, there are O(n log n) time approximation algorithms with factors 8 [1], 3 [7], and 2 [8]. Recently Chin et al [9] proved that the decision version of the MMN problem is strongly NP-complete. Recently, Knauer et al [10] showed that this problem is fixed parameter tractable.…”
Section: Introductionmentioning
confidence: 99%
“…First note that, in view of the fact that the problem of computing a minimum Manhattan network is NP-hard [7] and the fact that there is always a minimum Manhattan network that is contained in the grid induced by the given point set (see e.g. [3]), we have: Proposition 6.…”
Section: Finding Minimal Subrealizationsmentioning
confidence: 99%
“…First, we consider a special instance of the problem where we take metrics to be l 1 -distances between points in the plane. In Section 5 we show that finding optimal realizations of such a metric D in G D is equivalent to the so-called minimum Manhattan network problem (which was also recently shown to be NP-hard [7]). This allows us to compare the realizations computed by our heuristic with realizations computed using a mixed integer linear program (MIP) for the minimum Manhattan network problem presented in [3] (see also [26] for a comprehensive list of references on other approaches for solving this well-studied problem).…”
Section: Introductionmentioning
confidence: 99%
“…For example, Wendell and Hurter [27] establish this type of results for the Weber problem (the weighted version of the median problem) while Hansen, Perreur, and Thisse [15] proved a similar result for the NP-hard multifacility location problem. In [6], it was shown that Pareto envelopes in the l 1 -plane contain at least one minimum Manhattan network, and this fact was used in all factor 2 approximation algorithms [6,12,14,19] for the NP-hard [7] minimum Manhattan network problem. For other results in this vein, see [23].…”
Section: Introductionmentioning
confidence: 99%